أثر استراتيجية الخرائط المعرفية في تحصيل مادة التاريخ عند طلاب الصف الرابع الأدبيّ - حميد مجيد فؤاد (Journal of College of Education, 2020)
The aim of the research is to identify the impact of the knowledge mapping strategy on the achievement of history for fourth literary students. The study sample reached (60) students. The researcher chose experimental design with partial control for the two research groups, and the two research groups were rewarded in a number of variables. The researcher prepared the achievement test, and the damaged test test was constructed from (46) paragraphs of the objective questions of the test type from multiple and (14) paragraphs from the essay questions. And its stability, and other statistical methods that used the t-test equation, the difficulty factor equation, the paragraph strength differentiation equation, and the effectiveness of alternatives, and in light of the research results, the researcher recommended a number of recommendations and proposals.